2018
DOI: 10.7717/peerj.4853
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sofosbuvir plus Ribavirin therapy on hepatitis C patients in Pakistan: a retrospective study

Abstract: BackgroundThe annual global deaths from viral hepatitis is 1.4 million. Pakistan has the second highest burden of hepatitis C in the world. There is dire need to evaluate the response of new direct acting antivirals for the treatment of hepatitis C patients in Pakistan. World Health Organization has developed a strategy to treat 80% of HCV patients by 2030. In Pakistan, HCV treatment rate is 1%. The aim of the study was to analyze the effect of Sofosbuvir plus Ribavirin therapy on HCV patients in Pakistan.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…All the patients achieved undetectable HCV RNA at the end of treatment (ETR). This was similar to the results reported by Jamil et al where 98.7% of patients achieved ETR [12]. Comparable results were reported by researchers from other countries [14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All the patients achieved undetectable HCV RNA at the end of treatment (ETR). This was similar to the results reported by Jamil et al where 98.7% of patients achieved ETR [12]. Comparable results were reported by researchers from other countries [14].…”
Section: Discussionsupporting
confidence: 92%
“…Almost 60 percent of the study population consisted of females. Our study was demographically comparable to other studies from Pakistan [11,12]. Most of the patients (78.4%) had a low socioeconomic status.…”
Section: Discussionsupporting
confidence: 87%
“…None of the patients required blood transfusion. During treatment, none of the patients had significant hepatic decompensation or hyperbilirubinemia of >2.5mg/dl.In one patient (1.1%) platelet count dropped to 44,000 per mm 3 at the 12 th week of treatment, from a pretreatment value of 90,000 per mm 3 . However, patient did not experience any abnormal bleeding and platelet count subsequently improved to 70,000 per mm 3…”
Section: Safetymentioning
confidence: 86%
“…In 2017, in the global hepatitis report by World Health Organization, it was noted that in year 2015; globally 720,000 deaths were due to various complications of advanced chronic liver disease whereas 470,000 were related to hepatocellular carcinoma 1 . An estimated 11.55% of the adult Pakistani population is affected by hepatitis C, of which upto 91.8% have genotype 3a 3 . Another study from Pakistan, which showed a dismal average survival of only 23.9 months for patients presenting with hepatocellular carcinoma, revealed 84.4% had evidence of hepatitis C infection 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no vaccine available against HCV, very effective drugs are available for the treatment of HCV. 6 After the clearance of HCV infection, the immune system of the person may not be able to clear a subsequent infection completely. Having a household contact with an HCV positive patient is also a risk factor.…”
Section: Introductionmentioning
confidence: 99%